Factors Affecting the Indifference of Players in Training for Competitions - Fatemeh Rahmati; Masoud Naderian Jahroni (Archives in Sport Management and Leadership)
The research aimed to analyze the factors affecting players' indifference in preparation exercises for the 2024 Taekwondo League competitions. This applied study employed a descriptive method. To identify influencing factors, semi-structured interviews were conducted with 26 individuals—including 13 athletes, 6 coaches, 3 club managers, and 4 referees—who were selected through purposive sampling based on their expertise and experience until theoretical saturation was achieved. Data collection tools included interviews and questionnaires, both validated through content validity and reliability measures. Data analysis was conducted in two phases: initially via open and axial coding of qualitative data, and subsequently using MICMAC software for structural modeling. Qualitative results led to the extraction of 31 conceptual codes across six main categories: managerial factors, club structure and policies, infrastructure, financial issues, environmental conditions, and motivational elements. Quantitative findings from MICMAC analysis showed that managerial and financial factors had the highest driving power, while motivational and infrastructure factors had the highest dependency. The infrastructure category, in particular, was identified as a critical dependent factor, meaning that even small changes in this domain could cause substantial systemic shifts. Based on the integrated findings, it is suggested that club managers prioritize managerial actions (e.g., respecting players’ dignity and addressing their basic needs) and financial mechanisms (e.g., timely bonuses) to improve athletes' motivational levels. This would eventually lead to reduced player indifference in professional training contexts. The findings also reflect the role of distributive justice in reducing perceived unfairness, which is a major cause of demotivation among players.